2017
DOI: 10.1111/cjag.12147
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting Willingness‐to‐Pay through Multiple Experimental Procedures: Evidence from Lab‐in‐the‐Field in Rural Ghana

Abstract: This paper has the objectives of (a) comparing estimated willingness‐to‐pay (WTP) across three elicitation mechanisms (a Becker‐DeGroot‐Marschak [BDM] auction, a kth price auction, and a choice experiment [CE]) and (b) examining how these vary by participation fee. The product under consideration is kenkey made with nutritious maize, biofortified with vitamin A, which gives it a distinct orange color, in contrast to the white and yellow varieties that are traditionally consumed. We use an experiment consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
0
15
1
Order By: Relevance
“…BDM is a widely applied auction‐like mechanism in consumer acceptance analyses in rural Africa (e.g., Banerji et al., ; De Groote et al., ; Hoffmann et al., ; Kiria et al., ; Morawetz et al., ). In a BDM mechanism, the individual places a bid, b , for the product on sale.…”
Section: Methodsologymentioning
confidence: 99%
See 4 more Smart Citations
“…BDM is a widely applied auction‐like mechanism in consumer acceptance analyses in rural Africa (e.g., Banerji et al., ; De Groote et al., ; Hoffmann et al., ; Kiria et al., ; Morawetz et al., ). In a BDM mechanism, the individual places a bid, b , for the product on sale.…”
Section: Methodsologymentioning
confidence: 99%
“…The prevailing market prices for half a Kongo (500 g), or 3 Nescafé cups (300 g), of gari in Oyo and Imo states, respectively, varied between ₦20 to ₦50 (US$1≈ ₦150 when the study was implemented). Based on recent studies on vitamin A biofortified orange sweet potato in Uganda (Chowdhury et al., ) and orange maize in Zambia (Meenakshi et al., ) and Ghana (Banerji et al., ), we anticipated effects of 15% or 20%, corresponding to ₦5 or ₦7 as well as a standard deviation of ₦30–₦35. Power calculations indicated that for the pooled data over the two states and for one‐tailed test, 450 (150*3) participants were required for the three treatments, resulting in 225 participants per state.…”
Section: Methodsologymentioning
confidence: 99%
See 3 more Smart Citations